2019
DOI: 10.1177/0018720819868122
|View full text |Cite
|
Sign up to set email alerts
|

Exoscore: A Design Tool to Evaluate Factors Associated With Technology Acceptance of Soft Lower Limb Exosuits by Older Adults

Abstract: Objective This pilot study proposed and performs initial testing with Exoscore, a design evaluation tool to assess factors related to acceptance of exoskeleton by older adults, during the technology development and testing phases. Background As longevity increases and our aging population continues to grow, assistive technologies such as exosuits and exoskeletons can provide enhanced quality of life and independence. Exoscore is a design and prototype stage evaluation method to assess factors related to percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
(102 reference statements)
0
21
0
Order By: Relevance
“…As AUTONOMYO was still a prototype at the time of the study there were clear restrictions to its use. Despite these limitations, the interdisciplinary collaboration using a qualitative approach in health psychology was particularly fruitful to move beyond functional considerations on acceptance underlined by recent literature [48,53], and provide psychosocial insight of LLE acceptance for everyday use in the context of gerontology. In this sense, our approach enabled us to further understand end-users' perspectives in inductive ways.…”
Section: Discussionmentioning
confidence: 99%
“…As AUTONOMYO was still a prototype at the time of the study there were clear restrictions to its use. Despite these limitations, the interdisciplinary collaboration using a qualitative approach in health psychology was particularly fruitful to move beyond functional considerations on acceptance underlined by recent literature [48,53], and provide psychosocial insight of LLE acceptance for everyday use in the context of gerontology. In this sense, our approach enabled us to further understand end-users' perspectives in inductive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Shore et al assessed factors associated with the adoption of a proposed exoskeleton for elderly people and reported that appearance was one factor determining the acceptance of the exoskeleton. (67) Talukder et al proved that better aesthetic quality and a more user-friendly interface would allow elderly people to better enjoy the use of wearable healthcare devices. (56) Moreover, Willius et al reported in detail on the different preferences of elderly female and male adults regarding wearable healthcare devices.…”
Section: Requirements Of Wearable Healthcare Devices For Elderly Peoplementioning
confidence: 99%
“…This assistive device features a modular and reconfigurable design of hips, knees and ankles actuators. The effectiveness of the assistance provided by this exosuit in terms of improvements to rehabilitation parameters has previously been proven [23,26,27], as has the comfort and acceptability [28,29].…”
Section: Introductionmentioning
confidence: 96%